Re-establishment of olfactory and taste functions - Welge-Lüssen, Antje (German Medical Science, 2005)
The incidence of olfactory disorders is appoximately 1-2% and they can seriously impact on the quality of life. Quantitative disorders (hyposmia, anosmia) are distinguished from qualitative disorders (parosmia, phantosmia). Olfactory disorders are classified according to the etiology and therapy is planned according to the underlying pathophysiology. In ENT patients olfactory disorders caused by sinonasal diseases are the most common ones, followed by postviral disorders. Therapy consists of topical and systemic steroids, whereas systemic application seems to be of greater value. It is very difficult to predict the improvement of olfactory function using surgery, moreover, the long term - success in surgery is questionable. Isolated taste disorders are rare and in most often caused by underlying diseases or side effects of medications. A meticulous history is necessary and helps to choose effective treatment. In selected cases zinc might be useful.